2005
DOI: 10.1038/sj.bjc.6602649
|View full text |Cite
|
Sign up to set email alerts
|

Randomised phase II evaluation of irinotecan plus high-dose 5-fluorouracil and leucovorin (ILF) vs 5-fluorouracil, leucovorin, and etoposide (ELF) in untreated metastatic gastric cancer

Abstract: An open-label randomised comparison of efficacy and tolerability of irinotecan plus high-dose 5-fluorouracil (5-FU) and leucovorin (LV) (ILF) with etoposide plus 5-FU/LV (ELF) in patients with untreated metastatic or locally advanced gastric cancer. One cycle of ILF comprised six once-weekly infusions of irinotecan 80 mg m À2 , LV 500 mg m À2 , 24-h 5-FU 2000 mg m À2 , and ELF comprised three once-daily doses of etoposide 120 mg m À2 , LV 300 mg m À2 , 5-FU 500 mg m À2 . In all, 56 patients received ILF and 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 26 publications
3
42
0
4
Order By: Relevance
“…Irinotecan and taxane-based regimens have been used in the treatment of advanced gastric cancer patients, with survival times similar to those attained with FOLFOX (Moehler et al, 2005;Oh et al, 2007;Takayama et al, 2007). However, the short survival attained in FOLFOX-treated patients with positive protein ERCC1 (HR, 1.91) (Kwon et al, 2007) or overexpression of ERCC1 mRNA (HR, 9.4) suggests that irinotecan or taxane-based regimens could be the better alternative for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Irinotecan and taxane-based regimens have been used in the treatment of advanced gastric cancer patients, with survival times similar to those attained with FOLFOX (Moehler et al, 2005;Oh et al, 2007;Takayama et al, 2007). However, the short survival attained in FOLFOX-treated patients with positive protein ERCC1 (HR, 1.91) (Kwon et al, 2007) or overexpression of ERCC1 mRNA (HR, 9.4) suggests that irinotecan or taxane-based regimens could be the better alternative for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The first phase II study results suggested that irinotecan and 5-fluorouracil combinations had promising antitumoral activity and efficacy [49,50]. A randomized controlled phase III trial failed to show the superiority of irinotecan and high-dose 5-fluorouracil over only cisplatin and 5-fluorouracil [51].…”
Section: Irinotecan-containing Regimensmentioning
confidence: 99%
“…Three randomized trials tested treatment combinations of infused 5-FU and irinotecan [7,17,18]. A phase III trial randomized 333 patients to irinotecan plus high-dose 5-FU and leucovorin (IF) or cisplatin and 5-FU (CF).…”
Section: Discussionmentioning
confidence: 99%